Production of recombinant Bordetella pertussis serotype 2 fimbriae in Bordetella parapertussis and Bordetella bronchiseptica: utility of Escherichia coli gene expression signals. - Walker, M J (1991)
Serotype-specific fimbriae of Bordetella pertussis are considered potential components of new-generation vaccines against whooping cough. Attempts to characterize fimbriae, and indeed other virulence determinants, produced by B. pertussis have been frustrated on one hand by low yields from B. pertussis itself and on the other by an inability to produce native recombinant products in Escherichia coli. In order to try to circumvent this problem, we have examined the expression of B. pertussis serotype 2 fimbriae in Bordetella parapertussis and Bordetella bronchiseptica from native as well as E. coli expression signals. These studies revealed that the fimbrial gene product was expressed from the original B. pertussis promoter and Shine-Dalgarno sequence in both B. parapertussis and B. bronchiseptica. The transcriptional start site of the gene was located 146 nucleotides upstream of its ATG start codon. A recombinant fimbrial subunit gene containing PLAC and the atpE translation initiation region of E. coli was also expressed in B. bronchiseptica. In all cases in which gene expression was detected the gene product was expressed as serotype 2-specific fimbriae as determined by enzyme-linked immunosorbent assay (ELISA) and immunoelectron microscopic investigation of the bacterial cell surface.